Genetic polymorphisms of cytochrome p4502E1 and susceptibility to alcoholic liver disease and hepatocellular carcinoma in a white population: a study and literature review, including meta-analysis. Issue 2 (1st April 2000) - Wong, N A C S; Rae, F; Simpson, K J; Murray, G D; Harrison, D J
Abstract : Aims —To investigate the associations between the Rsa I, Dra I, and Taq I genetic polymorphisms of cytochrome p4502E1 and susceptibility to alcoholic liver disease or to hepatocellular carcinoma. Methods —DNA samples isolated from 61 patients with alcoholic liver disease, 46 patients with hepatocellular carcinoma, and 375 healthy controls were subjected to polymerase chain reaction amplification followed by digestion with the endonucleases Rsa I, Dra I, or Taq I. Meta-analysis was performed using data from previous studies of Rsa I polymorphism and the risk of alcoholic liver disease. Results —No association was found between any of the three polymorphisms and susceptibility to hepatocellular carcinoma. The distributions of Rsa I and Dra I alleles among the patients with alcoholic liver disease were not significantly different from those among the control group. Meta-analysis of this data and previous data concerning Rsa I polymorphism and alcoholic liver disease risk failed to demonstrate any significant association between the two. However, the alcoholic liver disease group in this study showed a significantly lower frequency of the less common Taq I allele compared with the healthy control group (odds ratio, 0.33; 95% confidence interval, 0.12 to 0.78). Conclusions —Possession of the less common Taq I cytochrome p4502E1 allele is associated with reduced susceptibility to alcoholic liver disease. There is no existing evidence that the Taq I polymorphism is directly associated with altered alcohol metabolism, but it might be in linkage disequilibrium with as yet unidentified protective factors.